Yield and Nitrogen Management of Irrigated Switchgrass Systems in Diverse Ecoregions. (1st March 2013) - Pedroso, Gabriel M.; Hutmacher, Robert B.; Putnam, Daniel; Wright, Steven D.; Six, Johan; van Kessel, Chris; Linquist, Bruce A.
Abstract : Climate trends and foreign oil dependency have led to a search for alternative sources of energy, such as biomass energy crops. Switchgrass ( Panicum virgatum L.) has shown promise as a high yielding energy crop in the United States. The objectives of this study were to evaluate cultivar Trailblazer switchgrass adaptability, biomass yield potential, and response to N fertilization in different ecoregions. Experiments were established in four ecoregions of California in 2007, with five N fertilizer treatments (0 to 300 kg N ha −1 yr −1 ) imposed from 2008 through 2010. The northern‐most and coolest temperate continental climate location was terminated after 2009 due to appreciable winter mortality. Yields ranged from 13 to 27.1 Mg ha −1 yr −1 across locations and years, with greatest yields in the warmer Mediterranean and semiarid climates of the Central Valley and the Desert climate region. Yield response to N was limited in 2008. However, in 2009 and 2010, yields increased linearly in three of four locations, indicating that greater yields could have been possible with greater N fertilization rates. On average across locations, the greatest N rate increased yields by 9.7 and 13 Mg ha −1 yr −1 and agronomic N use efficiency averaged 30 and 44 kg biomass kg −1 N applied in 2009 and 2010, respectively. Average crop N removal was 150 kg N ha −1 yr −1 for multi‐harvest systems, with the first harvest representing 70% of annual yields and 75% of crop N removal. Our results showed that in warm ecoregions with greater yield potential Trailblazer switchgrass required great N fertilization to sustain yields.